NILAI-NILAI AKSIOLOGIS DALAM FILSAFAT PENDIDKAN ISLAM - Atina; Siti Imroatul Latifah; Sefti Triani; Ahmad Suradi; Dayun Riadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic education aims to spread understanding comprehensively. This is useful for the formation of students' character and morals based on the rules that apply in philosophy. In the study of philosophy, axiology is a branch that focuses on values ​​and their meaning in life, including in the context of education. Axiological values ​​in Islamic education are not only related to ethics and morals, but also examine the principles of epistemology and aesthetics that shape the perspective and behavior of students. Based on research conducted using a qualitative descriptive approach with literature studies and concept analysis. Data sources consist of various literature related to Islamic educational philosophy, axiology, and contemporary educational theories. This study produces a study of Islamic education based on axiological values ​​that emphasize the justice of every knowledge, faith, and charity. These values ​​include honesty, responsibility, justice, and aesthetics in learning that inspire students to apply knowledge with moral and ethical principles.